2012
DOI: 10.1136/bmjopen-2011-000369
|View full text |Cite
|
Sign up to set email alerts
|

Emergency and surgery services of primary hospitals in the United Republic of Tanzania

Abstract: ObjectiveThe primary objective was to evaluate the capacity of first-referral health facilities in Tanzania to perform basic surgical procedures. The intent was to assist in planning strategies for universal access to life-saving and disability-preventing surgical services.DesignCross-sectional survey.SettingFirst-referral health facilities in the United Republic of Tanzania.Participants48 health facilities.MeasuresThe WHO Tool for Situational Analysis to Assess Emergency and Essential Surgical Care was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 8 publications
8
92
1
Order By: Relevance
“…Our findings identified the gaps in the infrastructure, human resources, surgical interventions, and essential equipment and indicated that suitable facilities and equipment, human resources, and infrastructure are available in the district hospitals in Iran at a standard higher than that in many of the LMICs which have evaluated and published the status of their own essential surgical care (11)(12)(13)(14)(15)(16)(17). Our results also showed a significant improvement in status by comparison with the situation 5 years ago in Iran.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our findings identified the gaps in the infrastructure, human resources, surgical interventions, and essential equipment and indicated that suitable facilities and equipment, human resources, and infrastructure are available in the district hospitals in Iran at a standard higher than that in many of the LMICs which have evaluated and published the status of their own essential surgical care (11)(12)(13)(14)(15)(16)(17). Our results also showed a significant improvement in status by comparison with the situation 5 years ago in Iran.…”
Section: Discussionsupporting
confidence: 68%
“…This tool is used to assess surgical needs in many developing countries and has been translated into Farsi and validated and employed in Iran by Mouseli (2009) (10)(11)(12). However, the researcher improved and completed the translation of the tool before it was utilized.…”
Section: Methodsmentioning
confidence: 99%
“…The hospitals that we investigated were all tertiary-care institutions and in most low-and middle-income countries there are many peripheral hospitals for each such tertiary-care institution. The peripheral rural hospitals are particularly likely to have low resources 27 and patients attending such hospitals with fractured femurs are more likely to be treated with traction than with intramedullary nailing. Our data probably therefore underestimate the mean length of time it would take a patient with a fractured femur to flow through a trauma system in a low-or middleincome country.…”
Section: Researchmentioning
confidence: 99%
“…5,26 The admission to surgery interval is affected by in-hospital variables such as the availability of human resources and essential equipment and the hospital infrastructure. 27 The final surgery to discharge interval may be affected by medication availability, nursing care, rehabilitation and the postoperative availability of social services. 28,29 This study proposes that the intervals from injury to admission, admission to surgery and/or surgery to discharge in the care of traumatic, isolated fractures of the femoral shaft can be good indicators of the general quality of musculoskeletal trauma services and can be validated as indicators against national economic and health system parameters, which are the best available data for such validation.…”
Section: Researchmentioning
confidence: 99%
“…1 It is recognized that surgery and anaesthesia services in low-and middle-income countries (LMICs) are un-der-equipped and under-staffed. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Most of this data comes from assessments of personnel, supplies and workload at institutions throughout the low resource world. It clearly demonstrates that surgical and anaesthesia services are unable to meet the current need, but gives no sense as to the true extent and nature of unmet need.…”
Section: Introductionmentioning
confidence: 99%